Multiscale Investigations of RC Shear Wall Buildings. Issue 10 (27th July 2022) - Tong, Tong; Bazroun, Mohammed; Cho, In Ho; Porter, Keith A.
ABSTRACT: The precise description of reinforced concrete shear wall (RCSW) systems under severe dynamic loading remains a difficult research question owing to the intrinsically multi-scale underlying mechanisms, ranging from building's irregularity to individual core walls, and even to the millimeter length-scales nonlinear shear over cracks and progressive steel bar buckling. This study adopted a parallel multiscale finite element analysis platform that can link the millimeter-level microphysical phenomena to the entire building-level dynamic responses in order to analyze weak pre-1980 buildings that lack modern codes such as boundary elements of walls. Results offer physically sound rationales behind the multi-scale damage behaviors.